A Protein Aggregation Inhibitor, Leuco-Methylthioninium Bis(Hydromethanesulfonate), Decreases α-Synuclein Inclusions in a Transgenic Mouse Model of Synucleinopathy - Schwab, Karima; Frahm, Silke; Horsley, David; Rickard, Janet E.; Melis, Valeria; Goatman, Elizabeth A.; Magbagbeolu, Mandy; Douglas, Morag; Leith, Michael G.; Baddeley, Thomas C.; Storey, John M. D.; Riedel, Gernot; et al. (Frontiers in Molecular Neuroscience, 2018)
alpha-Synuclein (alpha-Syn) aggregation is a pathological feature of synucleinopathies, neurodegenerative disorders that include Parkinson’s disease (PD). We have tested whether N,N,N’,N’-tetramethyl-10H-phenothiazine-3,7-diaminium bis(hydromethanesulfonate) (leuco-methylthioninium bis(hydromethanesulfonate); LMTM), a tau aggregation inhibitor, affects alpha-Syn aggregation in vitro and in vivo. Both cellular and transgenic models in which the expression of full-length human alpha-Syn (h-alpha-Syn) fused with a signal sequence peptide promotes alpha-Syn aggregation were used. Aggregated alpha-Syn was observed following differentiation of N1E-115 neuroblastoma cells transfected with h-alpha-Syn. The appearance of aggregated alpha-Syn was inhibited by LMTM, with an EC50 of 1.1 micromolar, with minimal effect on h-alpha-Syn mRNA levels being observed. Two independent lines of mice (L58 and L62) transgenic for the same fusion protein accumulated neuronal h-alpha-Syn that, with aging, developed into fibrillary inclusions characterised by both resistance to proteinase K (PK)-cleavage and their ability to bind thiazin red. There was a significant decrease in alpha-Syn-positive neurons in multiple brain regions following oral treatment of male and female mice with LMTM administered daily for 6 weeks at 5 and 15 mg MT/kg. The early aggregates of alpha-Syn and the late-stage fibrillar inclusions were both susceptible to inhibition by LMTM, a treatment that also resulted in the rescue of movement and anxiety-related traits in these mice. The results suggest that LMTM may provide a potential disease modification therapy in PD and other synucleinopathies through the inhibition of alpha-Syn aggregation.